The equation which is equivalent to
is
or x = 6 (
).
Explanation:
Given Equation:
![\log _(x) 36=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bjv3z0fbnvvl5qss4x03kxcafnap6laa5n.png)
As we know, in terms of logarithmic rules, when b is raised to the power of y is equal x:
![b^(y)=a](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7wdbnltw4yeftkdf2afo8ly14lv3hwpj75.png)
Then, the base b logarithm of x is equal to y
![\log _(b)(x)=y](https://img.qammunity.org/2021/formulas/mathematics/middle-school/etb332nv86ga17ees5559xy9xmj25e9q6e.png)
Now, use the logarithmic rule for the given equation by comparing with above equation. We get b = x, y = 2, and x = 36. Apply this in equation,
![b^(y)=a](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7wdbnltw4yeftkdf2afo8ly14lv3hwpj75.png)
![x^(2)=36](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ztnf2slvncjqoyxsurxo7lubgz25pxyxk9.png)
When taking out the squares on both sides, we get x = 6. Hence, the given equation can be written as
![\log _(6) 36=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/w4ga9vt49mfr6f4isa19n1k12cc7svss2a.png)